Cost of Good Manufactured (COGM) Calculation Using Activity-Based Costing Method in Manufacturing Companies: A Case Study of CV. YYY - Ikhsan Prasetyo; Muhammad Rafie Pasya; Alya Chaerunisa (International Journal of Marketing & Human Resource Research, 2026)
One of the most challenging issues faced by the manufacturing industry is managing production process costs, particularly in companies with a high variety of products. The use of conventional costing methods, which allocate overhead costs to a single cost driver, often fails to reflect actual production conditions, resulting in reduced accuracy in determining the Cost of Goods Manufactured (COGM). CV. YYY, as a multi-product manufacturing vendor, faces similar issues due to process complexity and the shared use of machinery, resulting in disproportionate cost calculations. This study applies the Activity-Based Costing (ABC) method to calculate COGM for eight product types. Data was obtained through observation, interviews, and documentation, then analyzed by six stages such as: identifying activities and activity cost pools, identifying direct and indirect costs, allocating indirect costs to each activity pool, determining cost drivers, calculating activity rates, and allocating costs to each product unit based on their respective cost drivers. The research results indicate that the ABC method provides more accurate and realistic cost calculations than the traditional method by allocating overhead costs proportionally based on actual activity consumption. Relying on traditional costing may distort unit production costs and pricing decisions; therefore, adopting ABC is essential for improved cost accuracy.